Pengolahan Ubi Ungu menjadi Cemilan Stik untuk Peningkatan Ekonomi Masyarakat Desa Tebing Linggahara - Teguh Fadillah Alwi Pasaribu; Luna Fadlillah Nathania Siregar; Dia Aulia (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the potential of processing purple sweet potatoes into stick-shaped snack products as an effort to improve the economy of Tebing Linggahara Village. Purple sweet potato is a local commodity with high nutritional value, antioxidant content, and promising market prospects when processed into modern snack products. The research method used was a descriptive approach consisting of observation, interviews, and direct product processing practices with the local community. The findings indicate that processing purple sweet potatoes into snack sticks provides higher economic value compared to selling fresh sweet potatoes, which generally have lower market prices. In addition, the community gained knowledge of food processing techniques, hygiene standards, packaging, and effective marketing strategies to enhance product competitiveness. Thus, purple sweet potato stick processing has the potential to serve as a sustainable local MSME development strategy, thereby improving the welfare and economic independence of Tebing Linggahara Village residents.